Islamic Stock Markets Integration and Contagion Effect of China’s Economic Slowdown - Harjum Muharam; M. Andika Jawara Pratama (Journal of Economics and Business, 2020)
This study investigated the existence of the Islamic stock markets integration among Asian countries and the contagion effect caused by the economics slowdown in China. The data of this study are the daily closing price of islamic stock index in Indonesia (MIID), Malaysia (MIMY), and China (MICN). The period of analysis is divided into tranquil period (August 30, 2007 - June 11, 2015) and turmoil period (June 12, 2015 - September 1, 2016). Meanwhile, there are 2351 observational datas used in this study. The Johansen Cointegration test, Vector Error Correction Model (VECM), and Granger Causality test are used as the research methods.The results showed that in both periods,the islamic stock market of three countries are integrated with each other. However, there is no evidence of contagion effect during the economics slowdown in China. In addition, there is a bidirectional causality relationship between the Malaysia and China Islamic stock markets.